Geriatric Acetabular Fractures and Femoral Head Protrusio: Methods of Fixation and the Option of Total Hip Arthroplasty. (October 2021) - Walters, Murphy M.; Bergin, Patrick F.; Russell, George V.; Morellato, John T.
Abstract : Summary: Currently, the literature is unclear regarding the optimal treatment algorithm for geriatric acetabular fractures. In a recent epidemiological study, 70% of all acetabular fractures in patients older than 65 years were classified as either associated both column or anterior column/posterior hemitransverse. Within the subset of these fractures, variants with significant femoral head protrusio, which is defined as the displacement of the femoral head medial to the ilioischial line, present with unique challenges. Goals of treatment in these cases should include surgical techniques that minimize the physiologic insult for the patient yet restore hip congruity and stability. "Fix and replace" is becoming an increasingly popular approach in the acute setting; however, its indications are not yet well-established. At our institution, we often favor open reduction and internal fixation alone as an effective and efficient way to treat the protrusio variant, even at the expense of protected weight-bearing. In the following article, we present a systematic approach for the management of geriatric acetabular fracture femoral head protrusio along with specific case examples.